Effect of delayed sea ice retreat on zooplankton communities in the Pacific Arctic Ocean: a generalized dissimilarity modeling approach - Hibino, Yuya; Matsuno, Kohei; Fujiwara, Amane; Abe, Yoshiyuki; Hosoda, Nanami; Itoh, Motoyo; Yamaguchi, Atsushi (Frontiers in Marine Science, 2025)
IntroductionSea ice extent increased in the Pacific Arctic Ocean during 2021 owing to the reversal of the Beaufort Gyre, unlike in previous years. The increased sea ice concentration may restore the marine ecosystem to its previous state; nevertheless, the precise conditions and mechanisms involved remain unclear.MethodsIn this study, the 2008–2017 period was defined as “the sea ice retreat year,” and its zooplankton community distribution representative was estimated using generalized dissimilarity modeling (GDM). Subsequently, we assessed the effect of delayed sea ice melt on the zooplankton community by comparing the zooplankton community of the sea ice retreat year with that in 2021.ResultsIn GDM, numerous satellite parameters significantly affected the zooplankton distribution, with the highest effect during the open-water period and annual primary production (APP) and the lowest in water temperature. The effect of APP and temperature on zooplankton similarity was high around the Bering Strait owing to the advection of Pacific copepods (Eucalanus bungii, Metridia pacifica, and Neocalanus spp.) and synchronized inflow of warm Pacific water. Under significant warming scenarios (Shared Socioeconomic Pathway [SSP]1-2.6 and SSP5-8.5), GDM-based multiple effects predicted that the zooplankton communities in high latitudes will be more affected than those on the southern shelf (northern Bering Sea to southern Chukchi Sea). In 2021, the total abundance across the northern Bering Sea to the Chukchi Sea shelf region was lower than that of the community during the sea ice retreat year. However, certain species (Limacina helicina and Pacific copepods) increased locally (northern Bering Sea and Barrow Canyon) because of the increasing volume of Pacific origin water.DiscussionContrary to the reported increase trend on zooplankton, low primary productivity and phenological mismatch for zooplankton may prevail in the Pacific Arctic Ocean, resulting in a low abundance during autumn 2021.